ECONOMICAL PATRIOTISM AS A PART OF NATIONAL IDEA IN THE CONDITIONS OF CLOBALIZATION - Костицький, В. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The article is devoted to the study of the content of the Ukrainian national idea, the consideration of globalization as an objective process of world development, as well as the problems of economic patriotism as the basis of the economic strategy of Ukraine in the era of globalization.